2011
DOI: 10.1111/j.1095-8649.2011.03071.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical wound healing in radio-tagged adult Pacific lamprey Entosphenus tridentatus held on different substrata

Abstract: Radio-tagged adult Pacific lamprey Entosphenus tridentatus held in a raceway with Plexiglas-lined walls and bottom healed more slowly and retained sutures longer than fish held in an all-concrete raceway or one with Plexiglas walls and a cobble-lined bottom. On all substrata, healing depended on when sutures were lost, and fish that lost their sutures in <14 days post-surgery healed faster than those that kept sutures longer. Long-term suture retention led to tissue trauma, infection and poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In adult lamprey, the presence of sutures can actually delay healing [23], and adults are routinely PIT-tagged without closing the incision [24]. We observed that wound closure could occur within 2 weeks for lamprey held in the laboratory at 14 °C, but that healing rates were quite variable among individuals.…”
Section: Discussionmentioning
confidence: 79%
“…In adult lamprey, the presence of sutures can actually delay healing [23], and adults are routinely PIT-tagged without closing the incision [24]. We observed that wound closure could occur within 2 weeks for lamprey held in the laboratory at 14 °C, but that healing rates were quite variable among individuals.…”
Section: Discussionmentioning
confidence: 79%
“…In comparison, 26% of radio-tagged lampreys in the Johnson et al (2012) study and 11% of those in Moser et al (2002) were never detected at Bonneville Dam after release downstream, on average. Potential effects include differences in handling stress (e.g., Close et al 2003) or increased susceptibility to postsurgery infection (e.g., Mesa et al 2011) during the later stage of migration or at the higher water temperatures lampreys encountered at McNary Dam relative to Bonneville Dam. However, we cannot rule out the possibility that capture, handling or tagging effects were higher for adults tagged at McNary Dam than for those tagged at Bonneville Dam.…”
Section: Sitementioning
confidence: 99%
“…However, we cannot rule out the possibility that capture, handling or tagging effects were higher for adults tagged at McNary Dam than for those tagged at Bonneville Dam. Potential effects include differences in handling stress (e.g., Close et al 2003) or increased susceptibility to postsurgery infection (e.g., Mesa et al 2011) during the later stage of migration or at the higher water temperatures lampreys encountered at McNary Dam relative to Bonneville Dam. It is also possible that monitoring fish at the same location where they were first collected affected lamprey behaviours or passage routes through avoidance or learned effects.…”
Section: Sitementioning
confidence: 99%
“…This study operated under the assumptions that the behaviour and survival of the tagged lamprey was not affected differently from the larger, untagged population, and none of the tags were shed. Surgery and tag effects on adult Pacific lamprey have been considered extensively by other researchers in the laboratory (Close et al, 2003;Mesa et al, 2003Mesa et al, , 2011 and in the field (Moser et al, 2007). These studies suggest that while tag effects cannot be completely ruled out, these effects on lamprey behaviour are minimal.…”
Section: Utility Of Using Translocated Lamprey For Dam Passage and Be...mentioning
confidence: 99%